THE IMPACT OF GENDER ON THE ARABIC LANGUAGE IN THE INTERPRETATION OF RELIGIOUS TEXTS ACCORDING TO NASR HAMID ABU ZAYD - Yusroh Yusroh; Fitria Sari Yunianti (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2020)
This paper discusses the impact of gender on the Arabic language in the interpretation of religious texts according to Nasr Hamid Abu Zayd, which relates to the jurisprudence of contemporary Muslim women in a gendered way through his contemporary reading of hermeneuticalism on the texts of the verses of the Qur'an, especially those related to the conditions of Muslim women in his book Circles of Fear: Reading in the Discourse of Women. The search results are that some of his gender views can be studied from his studies on the provisions of provisions relating to women registered in Surat Al-Nisaa, which the topic is about marriage, divorce, polygamy, inheritance, hijab and nakedness. He saw that the articles on women need to be analyzed because there is equality between men and women and gender equality is one of the purposes of legislation.